Direct oral anticoagulants (DOAC) – Management of emergency situations - Lindhoff-Last, Edelgard (Hämostaseologie, 2017)
The worldwide increase in the aging population and the associated increase in the prevalence of atrial fibrillation and venous thromboembolism as well as the widespread use of direct oral anticoagulants (DOAC) have resulted in an increase of the need for the management of bleeding complications and emergency operations in frail, elderly patients, in clinical practice. When severe bleeding occurs, general assessment should include evaluation of the bleeding site, onset and severity of bleeding, renal function, and concurrent medications with focus on anti-platelet drugs and nonsteroidal anti-inflammatory drugs (NSAID). The last intake of the DOAC and its residual concentration are also relevant. The site of bleeding should be immediately localized, anticoagulation should be interrupted, and local measures to stop bleeding should be taken. In life-threatening bleeding or emergency operations immediate reversal of the antithrombotic effect may be indicated. If relevant residual DOAC-concentrations are expected and surgery cannot be postponed, prothrombin complex concentrate (PCC) and/or a specific antidote should be given. While idarucizumab, the specific antidote for dabigatran, has been recently approved for clinical use, the recombinant factor X protein andexanet alfa, an antidote for the reversal of inhibitors of coagulation factor Xa, and ciraparantag, a universal antidote, are not available. Future cohort studies are necessary to assess the efficacy and safety of specific and unspecific reversal agents in “real-life” conditions. This was the rationale for introducing the RADOA-registry (RADOA: Reversal Agent use in patients treated with Direct Oral Anticoagulants or vitamin K antagonists), a prospective non-interventional registry, which will evaluate the effects of specific and unspecific reversal agents in patients with life-threatening bleeding or emergency operations either treated with DOACs or vitamin K antagonists.
Keywords: direct oral anticoagulants; life-threatening bleeding; emergency operation; reversal agents; prothrombin complex concentrate (PCC); antidotes